Multilevel analysis of site, implant, and patient-level factors with peri-implant bleeding on probing: a cross sectional study - Sunil Kumar Nettemu; Sowmya Nettem; Vijendra Pal Singh; Sheila Shirley William; Shargunan Selvanthan Gunasekaran; Malathi Krisnan; Adinegara Lutfi Abas (SpringerOpen, 2021)
Abstract Aim This study was to evaluate the association between peri-implant bleeding on probing in peri-implant diseases and its association with multilevel factors (site specific factors, implant factors, and patient level factors). Methodology A cross-sectional study involved consented adult patients with ≥ 1 dental implant. Two calibrated operators examined the patients. BoP was outcome variable and peri-implant gingival biotype was principal predictor variable. The effects of site, implant, and patient level factors on BoP were assessed using a multilevel logistic regression model. Results Eighty patients for a total of 119 implants and 714 sites were included in the study. Bleeding on probing was observed in 42 implants (35.29%) with a significant higher risk observed in presence of gingival recession, thin peri-implant gingival biotype, duration of implant placement, smokers, and male patients. Conclusion Peri-implant bleeding on probing was associated with site specific, implant, and patient level factors.